Penetration pathways for a foliar fertilizer in Agave tequilana Weber var. Azul - Bejines Ramos, Galdino; González Eguiarte, Diego R. (Revista Mexicana de Ciencias Agrícolas, 2017)
This research aimed to contribute to the knowledge of the  penetration pathway of the foliar fertilizer 4-17-17 (NPK)  in blue agave. In 1.5-year-old blue agave plants, histological  sections were made to identify the main morphological  characteristics of the leaf. Leaves were sprayed with  the fertilizer-dye fast green solution plus naphthol blue  black (F-VR-ANN) and separately with the fertilizer-dye  calcofluor solution (FC). Histological sections were made  at 30, 60 and 120 min after application. The activities were  conducted at the Laboratory of Plant Histopathology of the  Postgraduate College in Agricultural Sciences, Campus  Montecillo, during the months of August and September  2013. Small vascular bundles scattered in the palisade  parenchyma and spongy parenchyma were observed. The  thickness of the cuticle varied according to the sampling  site within the leaf, on average, 17.1 μm in the apical part  and 19.1 μm in the middle part of the leaf. In the palisaded  parenchyma crystals were observed, probably of calcium  oxalate in the form of prisms. Evidence on the accumulation  of the F-VR-ANN solution suggests that the penetration  route was stomatal and cuticular, since accumulation was observed after 30 min after application to the cuticle and  120 min after in the parenchyma in palisade. Also, the  application of the F-C solution suggests a cuticular and  stomatal penetration, as there was fluorescence within  the epidermal cells 30 min after the application and 120  min after it was observed between and within the palisade  parenchyma cells. In this way, the results show that foliar  fertilization may be a viable option to supplement soil  fertilization.
Keywords: Agave tequilana Weber var.Azul; cuticle; fluorescence